Mitochondrial respiratory capacity and coupling control decline with age in human skeletal muscle - Porter, Craig; Hurren, Nicholas M.; Cotter, Matthew V.; Bhattarai, Nisha; Reidy, Paul T.; Dillon, Edgar L.; Durham, William J.; Tuvdendorj, Demidmaa; Sheffield-Moore, Melinda; Volpi, Elena; Sidossis, Labros S.; Rasmussen, Blake B.; et al. (American journal of physiology: endocrinology and metabolism, 2015)
Mitochondrial health is critical to physiological function, particularly in tissues with high ATP turnover, such as striated muscle. It has been postulated that derangements in skeletal muscle mitochondrial function contribute to impaired physical function in older adults. Here, we determined mitochondrial respiratory capacity and coupling control in skeletal muscle biopsies obtained from young and older adults. Twenty-four young (28 ± 7 yr) and thirty-one older (62 ± 8 yr) adults were studied. Mitochondrial respiration was determined in permeabilized myofibers from the vastus lateralis after the addition of substrates oligomycin and CCCP. Thereafter, mitochondrial coupling control was calculated. Maximal coupled respiration (respiration linked to ATP production) was lower in muscle from older vs. young subjects ( P < 0.01), as was maximal uncoupled respiration ( P = 0.06). Coupling control in response to the ATP synthase inhibitor oligomycin was lower in older adults ( P < 0.05), as was the mitochondria flux control ratio, coupled respiration normalized to maximal uncoupled respiration ( P < 0.05). Calculation of respiratory function revealed lower respiration linked to ATP production ( P < 0.001) and greater reserve respiration ( P < 0.01); i.e., respiratory capacity not used for phosphorylation in muscle from older adults. We conclude that skeletal muscle mitochondrial respiratory capacity and coupling control decline with age. Lower respiratory capacity and coupling efficiency result in a reduced capacity for ATP production in skeletal muscle of older adults.